Effects of Real Earnings Management and ESG Disclosure on the Cost of Debt with Political Connections as a Moderating Variable: Evidence from Listed Firms in Indonesia - Ramiz Firas; Antonius Ragil Kuncoro (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
As a crucial financial metric, the cost of debt measures the economic burden that a firm bears when using loans to fund its operations. Using a regression model, this study examines how real earnings management, ESG disclosure, political connections, and several control variables affect the cost of debt within the context of non-financial firms listed on the Indonesia Stock Exchange during the observation period from 2018 to 2021. The results reveal that real earnings management has a significant positive connection with the cost of debt, while ESG Disclosure does not have a significant negative relationship with the cost of debt. As a moderating variable, political connections have been shown to strengthen the positive relationship between real earnings management and the cost of debt. Similarly, political connections also strengthen the negative relationship between ESG Disclosure and the cost of debt. This study highlights the importance of using ethical and transparent financial practices and robust ESG disclosure in managing debt costs. The findings provide insight into the potential benefits of aligning financial and sustainability practices, which may result in improved financial performance, enhanced investor confidence, and reduced business financing costs.